Horizontal Inequalities and Post-Conflict Development
XIX, 346 p.
Keywords: This book evaluates the extent to which post-conflict reconstruction has addressed problems of horizontal inequalities through country case studies on Burundi, Rwanda, Nepal, Peru, Guatemala, Bosnia and Herzegovina, and Afghanistan, and four thematic studies on macro-economic policies, privatisation, PRSP's, and employment generation.